2003
DOI: 10.1124/jpet.102.048090
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Gender Bias: Rat Cytochrome P450 3A9

Abstract: Some members of the CYP3A subfamily show gender-dependent expression. Using quantitative real-time polymerase chain reaction, we report that female rats have 28-fold higher CYP3A9 mRNA levels than males in liver and 3.8-fold higher in lung. Furthermore, the CYP3A9 expression profile in kidney exhibits a regio-specific distribution, i.e., a 10-fold higher expression in cortex compared with medulla. Also, we observed tissue-specific estrogen regulation of the CYP3A9 message. Estrogen treatment caused a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Since 1932, gender-related differences in the way by which animals metabolise drugs have been reported [15]; in this respect, a clear sexual dimorphism in the expression of hepatic genes, including some members of the CYP3A subfamily, has been documented in rodents and, particularly, in rats [1,13,20,24,28,33,42,45]. In cattle and other domestic animals, possible gendereffects on pharmacokinetics, including P450 drug metabolism, have already been described [4,6,8,9,17,18,36,40,52].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1932, gender-related differences in the way by which animals metabolise drugs have been reported [15]; in this respect, a clear sexual dimorphism in the expression of hepatic genes, including some members of the CYP3A subfamily, has been documented in rodents and, particularly, in rats [1,13,20,24,28,33,42,45]. In cattle and other domestic animals, possible gendereffects on pharmacokinetics, including P450 drug metabolism, have already been described [4,6,8,9,17,18,36,40,52].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of genderspecific CYP isoforms in different species is, therefore, a first step in understanding gender-biased drug metabolism. 3 The genomic characterization of Cyp3a41 gene revealed an array of regulatory elements in the 5 0 flanking region including PXRE (ER6), HNF4, STAT5, CAAT and others. It has been recently reported that HNF4A knockout mice show lack of PXR gene expression, while hepatic conditional HNF4A deletion leads to reduced basal and inducible CYP3A expression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the role of E2 on CYP3A41 expression, female mice were ovariectomized and were treated with either estrogen (500 mg/kg) or sesame oil s.c. for a week. 3 At the end of the experiments, all mice including controls were killed, tissues excised, immediately frozen in liquid nitrogen, and stored at À801C until analyzed.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten micrograms of liver or intestinal ileum RNA was treated with DNase and reverse-transcribed with Superscript II (Invitrogen), and complementary DNAs were subjected to real-time PCR as described. 17 The PCR primer and probe sets were as follows: for Mrp4, forward primer 5Ј-tttacaagatggttcagcaactgg-3Ј, reverse primer 5Ј-ctgtccattggaggtgttcataac-3Ј, and probe 5Ј-cgaagccgctgccctcaccgaaac-3Ј; for Mdr1, forward primer 5Ј-gacttgatcgtggtgattgagaac-3Ј, reverse primer 5Ј-tggaccattgagaagtagatgcc-3Ј, and probe 5Ј-caaggagcacggcacccaccagc-3Ј; and for FGF15, forward primer 5Ј-gattgccatcaaggacgtcag-3Ј, reverse primer 5Ј-tcagcccgtatatcttgccg-3Ј, and probe 5Ј-tgcggtacctctgcatgagcgc-3Ј.…”
Section: Methodsmentioning
confidence: 99%